Advanced in Vitro Safety Assessment of Herbal Medicines for the Treatment of Non-Psychotic Mental Disorders in Pregnancy - Spiess, Deborah; Winker, Moritz; Dolder Behna, Alexandra; Gründemann, Carsten; Simões-Wüst, Ana Paula (Frontiers in Pharmacology, 2022)
When confronted with non-psychotic mental disorders, pregnant women often refrain from using synthetic drugs and resort to herbal medicines such as St. John's wort, California poppy, valerian, lavender, and hops. Nevertheless, these herbal medicines have not yet been officially approved in pregnancy due to lack of safety data. Using a variety of in vitro methods (determination of cytotoxicity, apoptosis induction, genotoxicity, effects on metabolic properties, inhibition/induction of differentiation) in a commonly used placental cell line (BeWo b30), we were previously able to show that extracts from these plants are likely to be safe at the usual clinical doses. In the present work, we wanted to extend our safety assessment of these herbal medicines by (i) looking for possible effects on gene expression and (ii) using the same in vitro methods to characterize effects of selected phytochemicals that might conceivably lead to safety issues. Proteomics results were promising, as none of the five extracts significantly affected protein expression by up- or down-regulation. Protopine (contained in California poppy), valerenic acid (in valerian), and linalool (in lavender) were inconspicuous in all experiments and showed no adverse effects. Hyperforin and hypericin (two constituents of St. John's wort) and valtrate (typical for valerian) were the most obvious phytochemicals with respect to cytotoxic and apoptotic effects. A decrease in cell viability was evident with hypericin (≥ 1 µM) and valtrate (≥ 10 µM), whereas hyperforin (≥ 3 µM), hypericin (30 µM) and valtrate (≥ 10 µM) induced cell apoptosis. None of the tested phytochemicals resulted in genotoxic effects at concentrations of 0.1 and 1 µM and thus are not DNA damaging. No decrease in glucose consumption or lactate production was observed under the influence of the phytochemicals, except for valtrate (at all concentrations). No compound affected cell differentiation, except for hyperforin (≥ 1 µM), which had an inhibitory effect. This study suggests that extracts from St. John's wort, California poppy, valerian, lavender, and hops are likely to be safe during pregnancy. High plasma concentrations of some relevant compounds – hyperforin and hypericin from St. John's wort and valtrate from valerian – deserve special attention, however.